Medically Refractory Neuroborreliosis Case Presented with Coexistance Involvements of Cranial 7 and 8 Nerves - Anam Hareem; Iman Dabiri; Nida Zaheer; Ahmet Z. Burakgazi (MDPI AG, 2021)
In the US, Lyme disease (LD) has become the most common vector-borne disease. Less than 10% of patients develop cranial nerve palsy or meningitis. There are few reports on cases of Lyme disease with more than one cranial neuropathy. Herein, we will discuss a case of persistent neurological deficits as a result of chronic Lyme disease resistant to standard therapy. Our case is unique due to involvements of cranial seven and eight nerves at the same time. Our case illustrates an extreme example of treatment resistance. However, early diagnosis and prompt establishment of adequate antibiotic treatment are still important to prevent progression to further stages of disease.